Slovenian Validation of the Children’s Perceived Use of Self-Regulated Learning Inventory - Komidar, Luka; Podlesek, Anja; Pirc, Tina; Pečjak, Sonja; Depolli Steiner, Katja; Puklek Levpušček, Melita; Gril, Alenka; Boh Podgornik, Bojana; Hladnik, Aleš; Kavčič, Alenka; Bohak, Ciril; Lesar, Žiga; et al. (Frontiers in Psychology, 2022)
The importance of self-regulated learning has increased during the COVID-19 pandemic and measures for assessing students’ self-regulation skills and knowledge are greatly needed. We present the results of the first thorough adaptation of the Children's Perceived use of Self-Regulated Learning Inventory. The inventory, consisting of 15 scales measuring nine components of self-regulated learning, was administered to a sample of 541 Slovenian ninth graders. Confirmatory factor analyses supported internal structure validity of most components, but two components required some structural modifications. Internal consistency coefficients were acceptable for the majority of scale scores and were highly comparable to the original ones. While metric invariance across gender was confirmed, the scalar invariance of some scales needs further examination. Meaningful correlations with relevant externally assessed and self-reported self-regulation and school performance variables indicated good criterion validity of the inventory. The Slovenian version of the CP-SRLI thus proved to be a sufficiently valid and reliable instrument for assessing pupils’ learning self-regulation.